Soil fungal community is more sensitive than bacterial community to modified materials application in saline–alkali land of Hetao Plain - Xiaolong Bai; En Zhang; Jinmin Wu; Donghai Ma; Chaohui Zhang; Bangyan Zhang; Yunpeng Liu; Zhi Zhang; Feng Tian; Hui Zhao; Bin Wang (Frontiers in Microbiology, 2024)
Soil salinization has become a major challenge that severely threatens crop growth and influences the productivity of agriculture. It is urgent to develop effective management measures to improve saline–alkali soil. Thus, in this study, soil properties, microbial communities, and function under desulfurization gypsum (DE), soil amendment (SA), farm manure (FA), and co-application of desulfurization gypsum, soil amendment, and farm manure (TA) in a field experiment were examined by high-throughput sequencing. The results showed that the application of modified materials is an effective approach in improving saline–alkali soil, especially TA treatment significantly increased the content of available phosphorus (AP), available potassium (AK), soil organic matter (SOM), and alkaline hydrolysis nitrogen (AHN) and decreased pH, bulk density (BD), and electrical conductivity (EC). The application of modified materials resulted in notable enhancement in fungal diversity and altered the composition and structure of the fungal community. Conversely, the effect on the bacterial community was comparatively minor, with changes limited to the structure of the community. Regarding the fungal community composition, Ascomycota, Mortierellomycota, and Basidiomycota emerged as the dominant phyla across all treatments. At each taxonomic level, the community composition exhibited significant variations in response to different modified materials, resulting in divergent soil quality. The TA treatment led to a decrease in Mortierellomycota and an increase in Ascomycota, potentially enhancing the ability to decompose organic matter and facilitate soil nutrient cycling. Additionally, the sensitivity of fungal biomarkers to modified materials surpassed that of the bacterial community. The impact of modified materials on soil microbial communities primarily stemmed from alterations in soil EC, AP, AK, and SOM. FUNGuild analysis indicated that the saprotroph trophic mode group was the dominant component, and the application of modified materials notably increased the symbiotroph group. PICRUSt analysis revealed that metabolism was the most prevalent functional module observed at pathway level 1. Overall, the application of modified materials led to a decrease in soil EC and an increase in nutrient levels, resulting in more significant alterations in the soil fungal community, but it did not dramatically change the soil bacterial community. Our study provides new insights into the application of modified materials in increasing soil nutrients and altering soil microbial communities and functions and provides a better approach for improving saline–alkali soil of Hetao Plain.